Late-Holocene dynamics of sea-surface temperature and terrestrial hydrology in southwestern Africa. (May 2018) - Granger, Robyn; Meadows, Michael E; Hahn, Annette; Zabel, Matthias; Stuut, Jan-Berend W; Herrmann, Nicole; Schefuß, Enno
Southwest Africa is an important region for paleo-climatic studies, being influenced by both tropical and temperate climate systems and thus reflecting the interplay of variable controls. The aim of this study was to unravel the interaction of sea-surface temperature (SST) changes in the southernmost Benguela upwelling system with precipitation changes in South Africa's winter rainfall zone (WRZ) during the late Holocene. Therefore, a marine sediment core from the southernmost Benguela upwelling system was investigated to reconstruct climate changes in this region for the past ~2000 years. Grain size and geochemical analyses were conducted to reconstruct changes in fluvial sediment discharge and weathering intensity, while SST changes were estimated using alkenone paleo-thermometry. Results show that the southernmost Benguela behaves distinctly in comparison with the rest of the Benguela system reflecting amplified SST changes. Decreasing SSTs accompanied increasing river discharge during times of increased precipitation in the WRZ, reflecting northerly shifted westerly winds during austral winter. We infer a control of past SST changes by processes not analogous to modern processes driving seasonal SST changes by changes through upwelling intensity. The findings suggest that late-Holocene SST changes in the southernmost Benguela upwelling system and the precipitation in the WRZ were both driven by latitudinal shifts of the austral westerly wind belt and associated changes in advection of cold sub-Antarctic waters and/or changes in Agulhas leakage of warm Indian Ocean waters.